Huoshanmycins A‒C, New Polyketide Dimers Produced by Endophytic Streptomyces sp. HS-3-L-1 From Dendrobium huoshanense - Zhu, Youjuan; Kong, Yichao; Hong, Yu; Zhang, Ling; Li, Simin; Hou, Shurong; Chen, Xiabin; Xie, Tian; Hu, Yang; Wang, Xiachang (Frontiers in Chemistry, 2022)
Three new polyketide dimers named huoshanmycins A‒C (1–3) were isolated from a plant endophytic Streptomyces sp. HS-3-L-1 in the leaf of Dendrobium huoshanense, which was collected from the Cultivation base in Jiuxianzun Huoshanshihu Co., Ltd. The dimeric structures of huoshanmycins were composed of unusual polyketides SEK43, SEK15, or UWM4, with a unique methylene linkage. Their structures were elucidated through comprehensive 1D-/2D-NMR and HRESIMS spectroscopic data analysis. The cytotoxicity against MV4-11 human leukemia cell by the Cell Counting Kit-8 (CCK8) method was evaluated using isolated compounds with triptolide as positive control (IC50: 1.1 ± 0.4 μM). Huoshanmycins A and B (1, 2) displayed moderate cytotoxicity with IC50 values of 32.9 ± 7.2 and 33.2 ± 6.1 μM, respectively.